PENGARUH PEMBERIAN PUPUK KANDANG KAMBING DAN PUPUK ORGANIK CAIR TERHADAP PERTUMBUHAN DAN HASIL TANAMAN TERONG UNGU (Solanum melongena L.): Pupuk Kandang Kambing, Pupuk Organik Cair, Terong - selfi saputri, kristin; Santosa, Sartono Joko; Siswadi, Siswadi (Innofarm:Jurnal Inovasi Pertanian, 2024)
Research on the Effect of Giving Goat Manure and Liquid Organic Fertilizer on the Growth and Yield of Purple Eggplant Plants (Solanum melongena L). This research aims to determine the best dose for the growth and yield of purple eggplant (Solanum melongena L). This research was carried out on Jl. Ngudi Kaweruh, Karanglo Lor Village, Sukorejo District, Ponorogo Regency with an altitude of ± 119 meters above sea level with alluvial soil type. The research used the RAKL (Complete Randomized Block Design) with 2 treatment factors which were repeated 3 times and there were 16 treatment combinations. The first factor is the provision of goat manure, consisting of 4 levels, namely: without treatment (control), (200 g/plant), (400 g/plant), and (600 g/plant). The dosage of Nasa liquid organic fertilizer as the second factor consists of 4 levels, namely: without treatment (control), (1 ml/l), (2 ml/l), and (3 ml/l). The observation data was analyzed using analysis of variance (ANOVA) and continued with the BNT test with a level of 5%. The results of the study showed that goat manure had an effect on the parameters height of plant, number of leaves, number of fruit and weight of purple eggplant fruit, while Nasa liquid organic fertilizer had an effect on the parameters height of plant, number of leaves, number of fruit and weight of fruit. The interaction between giving goat manure 600 g/plant and nasa liquid organic fertilizer 3 ml/l effect on weight of fruit (392,50 g). A dose of goat manure of 600 g/plant gave the best results in height of plant (58.92 cm), number of leaves (26.08 pieces), number of fruit (3.33) and weight of fruit (333.63 g), while the fertilizer dose Nasa organic 2 ml/l gave the best results on height of plant (57.92 cm), number of leaves (27.04 pieces), dose of 3 ml/l with number of fruit (3.63 pieces) and weight of fruit (352.00 g ). Keywords: Goat Manure, Liquid Organic Fertilizer, Eggplant